Fluxes of CO2, CH4, and N2O in an alpine meadow affected by yak excreta on the Qinghai-Tibetan plateau during summer grazing periods - Lin, Xingwu; Wang, Shiping; Ma, Xiuzhi; Xu, Guangping; Luo, Caiyun; Li, Yingnian; Jiang, Gaoming; Xie, Zubin (Soil biology & biochemistry, 2009)
To assess the impacts of yak excreta patches on greenhouse gas (GHG) fluxes in the alpine meadow of the Qinghai-Tibetan plateau, methane (CH4), carbon dioxide (CO2), and nitrous oxide (N2O) fluxes were measured for the first time from experimental excreta patches placed on the meadow during the summer grazing seasons in 2005 and 2006. Dung patches were CH4 sources (average 586 μg m-2 h-1 in 2005 and 199 μg m-2 h-1 in 2006) during the investigation period of two years, while urine patches (average -31 μg m-2 h-1 in 2005 and -33 μg m-2 h-1 in 2006) and control plots (average -28 μg m-2 h-1 in 2005 and -30 μg m-2 h-1 in 2006) consumed CH4. The cumulative CO2 emission for dung patches was about 36-50% higher than control plots during the experimental period in 2005 and 2006. The cumulative N2O emissions for both urine and dung patches were 2.1-3.7 and 1.8-3.5 times greater than control plots in 2005 and 2006, respectively. Soil water-filled pore space (WFPS) explained 35% and 36% of CH4 flux variation for urine patches and control plots, respectively. Soil temperature explained 40-75% of temporal variation of CO2 emissions for all treatments. Temporal N2O flux variation in urine patches (34%), dung patches (48%), and control (56%) plots was mainly driven by the simultaneous effect of soil temperature and WFPS. Although yak excreta patches significantly affected GHG fluxes, their contributions to the whole grazing alpine meadow in terms of CO2 equivalents are limited under the moderate grazing intensity (1.45 yak ha-1). However, the contributions of excreta patches to N2O emissions are not negligible when estimating N2O emissions in the grazing meadow. In this study, the N2O emission factor of yak excreta patches varied with year (about 0.9-1.0%, and 0.1-0.2% in 2005 and 2006, respectively), which was lower than IPCC default value of 2%.